Equities. Special situations (Equities magazine, 1997)
Newsletter of the magazine Equities, which presents an in depth profile of a different business every month. Information includes investing tips, history, management, competition, finances, risks and contact points.
Keywords: Business enterprises : United States : Periodicals; Securities : United States : Periodicals; Ejournals : UML; United States : Commerce : Periodicals